A Stone Can Bounce on the Surface of Water: A Conceptual Physics Analysis Study of Students - Wattimena, Herman Semuel; Jamaludin, Jamaludin; Batlolona, John Rafafy (Journal of Science and Science Education, 2024)
Throwing a stone on the surface of the water has been a popular hobby for thousands of years, but in recent times, this phenomenon is rarely encountered in physics education. Flat and round stones are the best choice due to their favorable surface area, which creates a rebound when they collide with the water. However, the "magic angle" between the rotating stone and the water must be around 20 degrees to achieve the maximum number of bounces. This is an interesting phenomenon to explore, especially for students in rural areas who often visit rivers or beaches to play. Therefore, this study was conducted to analyze the conceptual understanding of physics students regarding the phenomenon of stones bouncing on the surface of water. This research is a qualitative study that analyzes students' responses through direct questions posed by the teacher. The study was conducted with 20 ninth-grade students at SMP Negeri 81 Maluku Tengah. The findings show that students have a very weak understanding of the physics concepts related to the stone-bouncing phenomenon. They are unable to explain the phenomenon scientifically because they are still influenced by answers based on local and cultural experiences. As a result, the teacher took action by engaging students in direct learning and providing clear explanations of the concepts. Consequently, students' conceptual understanding of physics improved, and they were able to explain the phenomenon scientifically